2011
DOI: 10.1103/physrevd.83.064022
|View full text |Cite
|
Sign up to set email alerts
|

Trumpet solution from spherical gravitational collapse with puncture gauges

Abstract: We investigate the stationary end state obtained by evolving a collapsing spherical star with the gauges routinely adopted to study puncture black holes. We compare the end state of the collapse with the trumpet solution found in the evolution of a single wormhole slice and show that the two solutions closely agree. We demonstrate that the agreement is caused by the use of the Gamma-driver shift condition, which allows the matter to fall inwards into a region of spacetime that is not resolved by the numerical … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
58
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 40 publications
(63 citation statements)
references
References 48 publications
5
58
0
Order By: Relevance
“…The end state of a spherical gravitational collapse asymptotically approaches the same trumpet solution found in vacuum simulations [21]. The agreement of end states is again caused by the spatial gauge condition, which allows the matter to fall inwards into a region of spacetime that is not resolved by the numerical grid.…”
Section: Fig 5 (Color Online)supporting
confidence: 64%
See 3 more Smart Citations
“…The end state of a spherical gravitational collapse asymptotically approaches the same trumpet solution found in vacuum simulations [21]. The agreement of end states is again caused by the spatial gauge condition, which allows the matter to fall inwards into a region of spacetime that is not resolved by the numerical grid.…”
Section: Fig 5 (Color Online)supporting
confidence: 64%
“…Puncture gauge conditions play a key role in the simulations of rotational collapse as they "automatically" handle the singularity formation and subsequent evolution [20,21]. Building on previous work and extending it, we have demonstrated that the end state of an axisymmetric collapse in the puncture gauge is the same as the one obtained from the evolution of a spinning puncture [22].…”
Section: Discussionmentioning
confidence: 53%
See 2 more Smart Citations
“…While the left panel of Fig. 13 shows that most of the rest-mass is dissipated away already by t = 0.65 ms (see discussion in [69] about why this happens), some of the matter remains on the grid near the singularity, anchoring there the magnetic field which slowly evolves as shown in the middle and right panels. A complementary view of the collapse process is also offered by Fig.…”
Section: Magnetized Collapse To a Black Holementioning
confidence: 99%